2006
DOI: 10.1116/1.2218852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N2 addition on density and temperature of radicals in 60MHz capacitively coupled c-C4F8 gas plasma

Abstract: Articles you may be interested inEffects of water addition on OH radical generation and plasma properties in an atmospheric argon microwave plasma jet Characterization of the behavior of chemically reactive species in a nonequilibrium inductively coupled argonhydrogen thermal plasma under pulse-modulated operation Behaviors of electrons and fluorocarbon radicals were investigated in 60 MHz capacitively coupled plasma employing mixture gases of c-C 4 F 8 , Ar, and N 2 . Optical emission spectroscopy was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Two photon excitations are used to detect of fluorescence that arises from atomic species such as O and Cl. 22,[27][28][29] VUVAS is used for the quantitative measurement of atomic species such as H, O, N, and C. [31][32][33][34][35][36][37][38][39] The energies for the optical transition from the ground level to the excited level of atomic species are in the range of VUV (wavelengths shorter than 200 nm). For measurements in the VUV range, a setup that eliminates atmospheric absorption is used.…”
Section: Process Monitoring Techniques For Gas-phase Measurementsmentioning
confidence: 99%
“…Two photon excitations are used to detect of fluorescence that arises from atomic species such as O and Cl. 22,[27][28][29] VUVAS is used for the quantitative measurement of atomic species such as H, O, N, and C. [31][32][33][34][35][36][37][38][39] The energies for the optical transition from the ground level to the excited level of atomic species are in the range of VUV (wavelengths shorter than 200 nm). For measurements in the VUV range, a setup that eliminates atmospheric absorption is used.…”
Section: Process Monitoring Techniques For Gas-phase Measurementsmentioning
confidence: 99%
“…We believe that this assumption will not strongly influence the main characteristics of this fc plasma source, since many experiments already revealed that light fc neutrals indeed dominate over heavy polymeric species in a C 4 F 8 plasma. [33][34][35][36] The F and CF 3 neutrals will recombine with themselves after sticking on the surface and return into the…”
Section: Model Descriptionmentioning
confidence: 99%
“…10) Furthermore, the addition of nitrogen (N 2 ) instead of oxygen (O 2 ) gas to fluorocarbon plasmas has been reported to be advantageous since p-SiOCH films would be damaged by vacuum ultraviolet (VUV) emissions and neutrals of oxidative species in the case of O 2 addition. [11][12][13][14] In fluorocarbon plasma etching, CF 3 þ ions play a key role in minimizing any damage caused by ion bombardment, in conjunction with ion energy and etching yield, since a low incident energy would be possible because of high etching yields obtained even at low bombardment energies. 15) Previously, Nagai et al proposed the use of perfluoro-…”
mentioning
confidence: 99%
“…wafers. 14) The chamber was 40 cm in diameter and 30 cm in height. The distance between the upper electrode and the substrate was 3.5 cm.…”
mentioning
confidence: 99%